The extent of coaching behaviour and practices in supervision processes of PhD students - Myezwa, H.; Geber, H. (South African Journal of Higher Education, 2023)
The extent to which coaching behaviour is practiced in PhD supervision is unknown. Supervision and elements of supervision have been studied extensively but not coaching and supervision. The aim of this study was to assess the extent to which coaching behaviours were practiced by supervisors while engaging with PhD students during supervision. A cross sectional survey using a self-administered structured questionnaire was used on an online platform (REDCap). Descriptive and correlational statistics were used to determine the extent to which each coaching and supervision phenomenon were practiced. Three hundred and eighty students registered for a PhD for longer than six months in a Faculty of Health Sciences were invited to participate in the study and 76 participated. Low to moderate levels in coaching behaviour and practice, personal support, supervisor availability and research academic support are reported. Personal support and the level of satisfaction with supervision were significant predictors of coaching behaviour and practice. This study established the extent of different supervisory behaviours and coaching behaviour and practice among supervisors. Coaching in this study was not practised largely with a third of the students interviewed experiencing coaching behaviour and practice.